Taxonomic and phylogenic appraisal of Pestalotiopsis linguae sp. nov., and a new record of P. nanjingensis from Pyrrosia lingua (Polypodiaceae) in Southern China - Li, Hua; Manawasinghe, Ishara S.; Zhang, Yunxia; Senanayake, Indunil C. (Phytotaxa, 2023)
Pyrrosia lingua (Thunb.); Farwell is an epiphytic fern belonging to Polypodiaceae. As a plant with high medicinal value, Py. lingua has been introduced and cultivated in worldwide. In this study, Py. lingua samples were collected in Guangzhou city, Guangdong Province, China, and endophytic fungal strains were obtained using tissue isolation. Isolated fungi were identified based on morphological characteristics and phylogenetic approaches. The phylogenetic analyses and pairwise homoplasy index was done using the sequence data of the internal transcribed spacer (ITS), beta-tubulin (tub2) and translation elongation factor 1-alpha gene (tef 1-α). Based on the combined approaches, a new species, Pestalotiopsis linguae and a new host record, P. nanjingensis have been identified. This is the first recorded Pestalotiopsis species on Py. lingua worldwide. The species descriptions and illustrations have been provided for the new species and the host record. The results of this study have an important contribution to understanding the endophytic fungal diversity of Py. lingua and provide an essential platform for better research on the application value of Py. lingua plants in the future.